CTIM-30. PHASE II TRIAL OF PEMBROLIZUMAB IN RECURRENT AND RESIDUAL HIGH-GRADE MENINGIOMAS. (12th November 2021) - Brastianos, Priscilla; Kim, Albert; Giobbie-Hurder, Anita; Lee, Eudocia Quant; Wang, Nancy; Eichler, April; Chukwueke, Ugonma; Forst, Deborah; Arrillaga-Romany, Isabel; Dietrich, Jorg; Lou, Kevin; Larson, Juliana; et al.
Abstract: INTRODUCTION: High-grade meningiomas are associated with significant neuro-cognitive morbidity and a poor prognosis. Systemic therapies, to date, have demonstrated minimal efficacy. We recently found that high-grade meningiomas harbor an immunosuppressive tumor microenvironment and that programmed cell death-ligand 1 (PD-L1) expression may contribute to the aggressive phenotype of these tumors. Therefore, we conducted a single-arm, open-label phase II trial evaluating efficacy of pembrolizumab, a PD-1 inhibitor, in a cohort of 24 patients with recurrent and progressive grade II and III meningiomas. METHODS: The primary endpoint was the rate of progression-free survival at 6 months. The trial distinguished between 6-month PFS (PFS-6) rates of 26% vs. 52%. If at least 10 patients demonstrated a 6-month PFS, among the 24 patients, the agent would be considered worthy of further study. This design has at least 88% power using an exact binomial test with a one-sided significance level of 0.1. RESULTS: Between November 2017 to December 2019, twenty-four patients were enrolled. The majority of the patients in our cohort were heavily pre-treated; prior to enrolling to the study, twenty patients underwent more than one surgical resection and twelve patients had received more than one round of radiotherapy. Our study met its primary endpoint and achieved a 6-month progression-free survival rate of 0.50 (90% exact CI: 0.32-0.68) and a median PFS of 8.3 months (90% CI: 4.1-12.9 months). For the twelve patients who achieved the PFS-6 primary endpoint, median PFS from the start of treatment was 17.3 months (90% CI: 9.7 – 24.3 months). Four patients had grade-3 or higher adverse events that were at least possibly treatment-related, including colitis, skin infection, encephalopathy and transaminitis. CONCLUSION: Our study achieved its primary endpoint. These results suggest that pembrolizumab exerts promising activity on these tumors and results in prolonged PFS compared to historical controls.